2018
DOI: 10.1007/s00705-018-3840-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and biological characterization of Newcastle disease viruses isolated from migratory mallards (Anas platyrhynchos)

Abstract: Given the global evolutionary dynamics of Newcastle disease viruses (NDVs), it is imperative to continue extensive surveillance, routine monitoring and characterization of isolates originating from natural reservoirs (waterfowls). In this report, we isolated and characterized two virulent NDV strains from clinically healthy mallard (Anas platyrhynchos). Both isolates had a genome of 15,192 nucleotides encoding six genes in an order of 3´-NP-P-M-F-HN-L-5´. The biological characteristics (mean death time: 49.5-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
(38 reference statements)
1
16
0
1
Order By: Relevance
“…Despite the use of imported vaccines, AAVV-1 still remains the main poultry disease in both commercial and rural chickens flocks of Pakistan [15]. Recently, AAVV-1 s of genotype VI, VII and XIII were detected in Pakistani poultry [16][17][18][19][20][21][22][23] and genotype VII is predominant across the country. Similarly, Miller et al [24] reported that viruses of sub-genotype VIIi have replaced AAVV-1 isolates of genotype XIII in Pakistan, which were commonly isolated since 2009-2011.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of imported vaccines, AAVV-1 still remains the main poultry disease in both commercial and rural chickens flocks of Pakistan [15]. Recently, AAVV-1 s of genotype VI, VII and XIII were detected in Pakistani poultry [16][17][18][19][20][21][22][23] and genotype VII is predominant across the country. Similarly, Miller et al [24] reported that viruses of sub-genotype VIIi have replaced AAVV-1 isolates of genotype XIII in Pakistan, which were commonly isolated since 2009-2011.…”
Section: Discussionmentioning
confidence: 99%
“…Across Pakistan, Avian avulavirus 1 strains of genotype VI (Akhtar et al 2016;Shabbir et al 2016), VII (Shabbir et al 2012a(Shabbir et al , b, 2013(Shabbir et al , 2016Munir et al, 2012a, b;Abbas et al 2014;Farooq et al 2014;Akhtar et al 2016;Habib et al 2018;Aziz-ul-Rahman et al 2018a and XIII (Miller et al 2015;Shabbir et al 2018) (Shabbir et al 2012;Munir et al 2012a, Qamar-un-Nisa et al 2017, Akhtar et al 2017, Israel and a public zoo in Mexico (Panshin et al 2002;Miller et al 2009). Therefore, the role of wild birds as natural reservoirs in dissemination of the virus cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Class-I contains nine distinct genotypes (I-IX) of avirulent strains that share a 15198 nt long genome, while class-II contains at least eighteen distinct genotypes (I-XVIII) of high virulent, low virulent and avirulent strains that have a 15186 and/or 15192 nt long genome (Aldous et al 2003;Kim et al 2007). Based on partial sequencing of F genes (375bp between 4597-4972 nts), avualviruses of genotypes I, II, VI, VII, XIII are further divided into different sub-genotypes of both virulent and avirulent strains isolated from a wide range of avian species (Shabbir et al 2012a(Shabbir et al , b, 2013(Shabbir et al , 2016Munir et al 2012a, b;Miller et al 2015;Akhtar et al 2016;Nath and Kumar 2015;Das andKumar 2017, Xue et al 2017;Barman et al 2017;Habib et al 2018;Aziz-ul-Rahman et al 2018a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waterfowl, the natural reservoir of NDVs, has the potential to spread the virus in the environment and within their susceptible hosts. It results in frequent ND outbreaks and subsequent economic losses [8][9][10]. Class I NDVs were originally recovered from both domestic and wild birds sampled in North America and Eurasia since at least the 1970s [6,11,12].…”
Section: Introductionmentioning
confidence: 99%